2002
DOI: 10.1080/10473289.2002.10470796
|View full text |Cite
|
Sign up to set email alerts
|

Degradation Characteristics of Toluene, Benzene, Ethylbenzene, and Xylene by Stenotrophomonas maltophilia T3-c

Abstract: Stenotrophomonas maltophilia T3-c, isolated from a biofilter for the removal of benzene, toluene, ethylbenzene, and xylene (BTEX), could grow in a mineral salt medium containing toluene, benzene, or ethylbenzene as the sole source of carbon. The effect of environmental factors such as initial toluene mass, medium pH, and temperature on the degradation rate of toluene was investigated. The cosubstrate interactions in the BTEX mixture by the isolate were also studied. Within the range of initial toluene mass (fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
43
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(50 citation statements)
references
References 14 publications
2
43
0
3
Order By: Relevance
“…Based upon this finding, the isolate was designated as Stenotrophomonas maltophilia M1 strain. It has been reported that S. maltophilia is able to degrade many xenobiotic compounds (Lee et al 2002) and to detoxify high molecular weight polycyclic aromatic hydrocarbons (Juhasz et al 2000). Therefore, it possesses a potential for soil decontamination (bioremediation).…”
Section: Characterization and Identification Of Methomyldegrading Isomentioning
confidence: 99%
“…Based upon this finding, the isolate was designated as Stenotrophomonas maltophilia M1 strain. It has been reported that S. maltophilia is able to degrade many xenobiotic compounds (Lee et al 2002) and to detoxify high molecular weight polycyclic aromatic hydrocarbons (Juhasz et al 2000). Therefore, it possesses a potential for soil decontamination (bioremediation).…”
Section: Characterization and Identification Of Methomyldegrading Isomentioning
confidence: 99%
“…It has, for instance, been isolated from the rhizosphere of various plants and animals (14,27,37). Due to its tolerance against cadmium and its ability to degrade xenobiotic compounds, it has been proposed for remediation of contaminated ground (9,39). Increasingly, it is being isolated from immunosuppressed individuals and intensive care and cystic fibrosis (CF) patients and has been shown to be resistant to many antimicrobial agents (16,17,69).…”
mentioning
confidence: 99%
“…The finding of a few Stenotrophomonas-related clones in the 13 C-labelled DNA clone library could indicate a broader diversity of triclosan degraders or the presence of multiple degradation steps catalysed by different micro-organisms. Although members of Stenotrophomonas have previously been shown to be involved in the degradation of environmental pollutants with aromatic structures such as p-nitrophenol (Liu et al, 2007), nonylphenol (Soares et al, 2003) and benzene (Lee et al, 2002), their involvement in degradation of triclosan was not confirmed by the MAR-FISH approach. Another betaproteobacterial group was found to be present in similar numbers to Methylobacillus and with similar triclosan degradation activity; however, these cells were not identified by the SIP approach.…”
Section: Discussionmentioning
confidence: 72%